Effectiveness of inactivated influenza vaccine in children by vaccine dose, 2013–18. Issue 30 (9th July 2019) - Shinjoh, Masayoshi; Sugaya, Norio; Furuichi, Munehiro; Araki, Eriko; Maeda, Naonori; Isshiki, Kyohei; Ohnishi, Takuma; Nakamura, Shoko; Yamada, Go; Narabayashi, Atsushi; Nishida, Mitsuhiro; Taguchi, Nobuhiko; et al.
Highlights: Both one- and two-doses regimens of inactivated flu vac are effective for children. Both regimens reduced cases involving hospitalization due to influenza A. The two-dose regimen was more effective against influenza B in some seasons. Abstract: Objectives: We assessed the vaccine effectiveness (VE) of inactivated influenza vaccine (IIV) by vaccine dose in children aged 6 months to 12 years for whom two doses are recommended in Japan to ascertain the appropriate vaccine doses. Methods: VE was assessed according to a test-negative case-control design based on rapid influenza diagnostic test (RIDT) results. Children aged 6 months to 12 years with a fever ≥38 °C who had received an RIDT in outpatient clinics of 24 hospitals were enrolled for all five seasons since 2013/14. VE by vaccine dose (none vs. once or twice, and once vs. twice) was analyzed. Results: In the dose analysis, 20, 033 children were enrolled. Both one- and two-dose regimens significantly reduced cases in preventing any influenza, influenza A, and influenza B, but there was no significant difference in adjusted VE between one- and two-dose regimens overall (adjusted OR, 0.560 [95% CI, 0.505–0.621], 0.550 [95% CI, 0.516–0.586]), 0.549 [95% CI, 0.517–0.583], and 1.014 [95% CI, 0.907–1.135], for none vs. once, none vs. twice, none vs. once or twice, and once vs. twice for any influenza, respectively). Both one- and two-dose regimens significantly reduced cases with any influenza and influenza A every season. Also, both regimens significantly reduced cases of any influenza, influenza A, and influenza B among children aged 1–12 years, especially among those aged 1–5 years. In the 2013/14, 2015/16, and 2016/17 seasons, however, only the two-dose regimen was significantly effective in preventing influenza B. Both one- and two-dose regimens significantly reduced cases involving hospitalization due to any influenza and influenza A. Conclusions: Both one- and two-doses regimens of IIV were effective in preventing influenza for children aged 6 months to 12 years. The two-dose regimen was more effective against influenza B in some seasons.